Wants and Activities in Marshall - Parsons, Talcott (Quarterly Journal of Economics, 1931)
I. Wants and Activities; Utility Theory and the Development of Character through the Exercise of Faculties, 102. — II. The Supplies of the Factors of Production, 113. — III. Real Costs, 119. — IV. Free Enterprise and Laissez-faire, 123. — V. Social Evolution, 128. — VI. The "Natural Order, " 132. — VII. Human Nature, 135. — Conclusion, 139.